Analisis Pengaruh Produk Domestik Regional Bruto, Indeks Pembangunan Manusia, dan Tingkat Pengangguran Terbuka terhadap Jumlah Penduduk Miskin Di Kabupaten Gresik - Putri Indah Sari; Sri Muljaningsih; Kiky Asmara (CV. Syntax Corporation Indonesia, 2021)
Poverty is a condition in which a person is unable to meet his daily needs because not all economic sectors can become the base sector, causing the income distribution to be low, and also due to the low quality of human life and the high unemployment rate. This study uses a research method with a quantitative approach. The data used in this study are secondary data and Time Series data from 2000-2019. The purpose of this study was to determine the effect of the Gross Regional Domestic Product, Human Development Index, and the Open Unemployment Rate on the Number of Poor People in Gresik Regency. The analysis technique in this research is using Multiple Linear Regression Analysis. The results in this study indicate that the Gross Regional Domestic Product Variables and Human Development Index have a negative and significant effect on the Number of Poor People, while the Open Unemployment Rate has a positive and significant effect on the Number of Poor People.